Perlindungan Hukum Data Pribadi dan Pertanggungjawaban Otoritas Terhadap Keamanan Siber Menurut Tinjauan UU PDP - Usman, Noval; Satria Unggul Wicaksana Prakasa (Universitas Medan Area, 2024)
The issue of cyber security and personal data in Indonesia is a problem that cannot be underestimated. The National Cyber ​​Security Index (NCSI) report noted that Indonesia's cyber security index score was 38.96 points out of 100 in 2022. This figure places Indonesia in the 3rd lowest ranking among the G20 countries. The legal issues in this research are: Responsibility of cyber security actors for leaks of personal data within a company and what form of legal protection in Indonesia exists in maintaining the security of personal data. The research method uses a socio-legal approach to identify IT and law. The results of this research show that cyber security actors in a company can be held accountable in accordance with Article 30 of the PDP Law and are responsible for leaking personal data and managing users' personal data within the company. The form of legal protection for individuals in safeguarding personal data is in the form of a legal product, Law Number 27 of 2022 (PDP Law).